Estudo da interação solo-muro em concreto convencional, com resíduo de construção e demolição (RCD) e alvenaria de pedra - Sá, Wallace Borges de (2006)
One of the main problems, in the Region Metropolitan of Recife (RMR), in the hillsides it is the disordered occupation, increasing the number of housings in risk areas. One of the solutions for the stabilization of the hillsides is the use of the construction of retained structure as support wall. The friction angle soil-wall is a basic parameter for the design of a support wall. Its value is used in the evaluation of the pushes active and passive in the analysis of stability of the wall. Practical the current one of projects in Brazil considers the value of the friction angle soil-wall as being equal to the angle of friction of the soil, a parcel of it or same zero to depend on the case. The values found in literature also indicate as estimative for this angle values that vary of zero to the angle of friction of the soil. Experimental values for Brazilian soils are not available in literature. Of this form the projects of support walls can be being designed against the security or of uneconomical form. In this context in the present dissertation tests of direct shear in specimens of composites of soil and another representative material of support walls had been carried through (conventional concrete, concrete with recycled aggregate of RCD and rock), with the objective to get the friction angle soil-wall. Two soils of the hillsides of Recife had been used (sandy and a other clayey one). The roughness of the surfaces in contact with soil had been evaluated, to analyze its influence in the interaction soil-wall. The gotten results are compared with values suggested in literature, having considered the influence of the soil and the roughness of the contact surface. The relation enters the friction angle soil-wall and the angle of friction of the ground (ä/ö) varies of 3/4 the 1, with the average roughness for the soil sandy of the Ibura and of 1/3 the 3/4 for the soil clayey of Nova Descoberta. In the soil sandy, the friction soil-wall has minor influence of the roughness of the faying surface and has value very next to the angle of internal friction of the soil. In the soil clayey the friction soil-wall strong is influenced by the roughness of the faying surface, and its value varies of 1/3 the 3/4 of the angle of friction of the soil